Assessment of scapular position measurement using ultrasound sensors to correct skin to bone artifacts from skin mounted motion capture - Vicini, A.; Sabick, M. B. (Computer Methods in Biomechanics and Biomedical Engineering: Imaging & Visualization, 2025)
Combining traditional motion capture markers with ultrasound sensors (MC+U) could enable accurate measurement of bone positions and orientations beneath the skin. This is especially important where skin-mounted markers are inaccurate, such as tracking scapular position when the shoulder is abducted over 80°. Previous in vitro research showed that the MC+U technique can be used to accurately track scapular position in static positions and when the shape of the subject`s scapula is known a priori from CT. This study extends those results in a more realistic in vivo setting. Scapula position and orientation were measured at five different humeral elevation angles in four subjects using MC+U and an acromial marker cluster (AMC). The results were compared to biplane fluoroscopy as the gold standard. The mean root mean square (RMS) error in scapular position with MC+U was 14±4 mm and 10±3°. When the arm was elevated 150° in the coronal plane, translational RMS error was only 9±3 mm for MC+U. These values represent a significant decrease in angular RMS error compared to the traditional AMC method in coronal plane motion, though larger than RMS errors in dual calibration methods. The MC+U technique shows promise for tracking scapular motion in dynamic multiplanar movements in vivo with further refinement.